The road to success: how regional innovation ecosystems can improve participation in the European Framework Programme for R&I - Océane Peiffer-Smadja; Alessio Mitra; Julien Ravet; Valentina Di Girolamo (Publications Office of the European Union, 2023)
This paper uses multiple linear and fractional probit regressions to assess the importance of regional research capacities and assets, as well as intrinsic characteristics of the regions in defining success in the European R&I Framework Programme. We find that quality of research outputs matters more than quantity, particularly in projects targeting societal challenges, while quality of patenting activity matters more than quantity, particularly in projects targeting industrial objectives. Less-developed regions benefit from improved institutions, while advanced regions gain from increased R&D and human resources investments. We provide recommendations on how regions can improve their capacity to participate in the EU FP for R&I.
Keywords: O38; R58; 330; European R&I Framework Programme; Regional innovation